1960
DOI: 10.1017/s0007485300057990
|View full text |Cite
|
Sign up to set email alerts
|

The white coffee borer, Anthores leuconotus Pasc., and its control.

Abstract: Anthores leuconotus Pasc., indigenous in East, South-East, South and South-West Africa, is an important ring-barking and wood-boring pest of the main stem and root of arabica coffee. The duration of the life-cycle ranges from 12 to 25 months, with most individuals requiring 16–20 months. Thus beetles developed from eggs laid during the long rains (April–June) of one year will mostly emerge during the short rains (Nov.–Jan.) of the following year, with some appearing during the rains preceding and others during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1975
1975
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…In fact, WCSB infestation is reported to be an issue of lower altitudes where mild temperatures prevail [ 67 ]. However, changes in climatic patterns resulted in the extension of coffee growing regions and hence a gradual spread of WCSB into higher elevations up to 1700 masl [ 68 ]. Climate trend analysis in Uganda has shown that over the past 25 years, rainfalls have decreased while temperatures have increased [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, WCSB infestation is reported to be an issue of lower altitudes where mild temperatures prevail [ 67 ]. However, changes in climatic patterns resulted in the extension of coffee growing regions and hence a gradual spread of WCSB into higher elevations up to 1700 masl [ 68 ]. Climate trend analysis in Uganda has shown that over the past 25 years, rainfalls have decreased while temperatures have increased [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study there was no evidence of any relationship between oviposition and trunk diameter except that produced by the bimodal distribution of oviposition sites with respect to height on the trunk. Some wood-boring Lamiinae, including the closely-related Anoplophora chinensis (Forster) [ ϭ A. malasiaca (Thomson); (Lingafelter and Hoebeke 2002)], attack almost exclusively near the base of the trunk (Ritchie 1920, Brooks 1923, Lieu 1945, Adachi and Korenaga 1989, Adachi 1990); other species prefer to attack higher on the trunk (Solomon 1972) and may distribute their attacks from ground level up to a height of several meters (Tapley 1961;Solomon 1972Solomon , 1974. In contrast, in our study A. glabripennis oviposited both near the base of the tree and higher on the trunk, but left a distinct gap between the base of the trunk and the bottom of the crown.…”
Section: Discussionmentioning
confidence: 99%
“…The adult males are more active fliers and travel long distance [ 13 , 59 , 70 ]. The pre-monsoon (April to May) to the post-monsoon period (October to November) is the window for the adult emergence from the bored hole [ 21 ].…”
Section: Adult Behaviourmentioning
confidence: 99%
“…The exposure of the borer to natural enemies is increased by proper shade management to maintain sunlight. Borers main enemies in the gallery are woodpeckers, green barbet and ants, so creating a conducive environment for their coexistence aids in borer management [ 70 ]. Microbial agents that attack the borer include Beauveria bassiana and Metarhizium anisopliae , which are most host-specific [ 37 , 70 ].…”
Section: Managementmentioning
confidence: 99%